‘Choosing the Gender We Feel We Are Is a Profound Choice’. Gender Identities and Sexual Orientations Among Young People - Guizzardi, Luca (Italian Sociological Review, 2024)
The purpose of this essay is to analyze the different representations of identity linked to sex, gender and sexual orientation in both academic and scientific debate and in the everyday life of young people. In the first part, three representations are discussed: that of coincidence, that of juxtaposition or denial and, finally, that of relative normality. The second part, on the other hand, presents the results of research on how young people aged between 18 and 33 define and forge their own sexual identity, with particular reference to gender and sexual orientation.